Responsive internal program evaluation as an quality monitoring mechanism alternative at HEI in Malaysia: A case study / Ahmad Saruddin Endut - Endut, Ahmad Saruddin (Institute of Graduate Studies, UiTM, 2018)
The exponential changes in technology and economic environment have resulted in greater changes to the educational landscape all over the world. These changes in the forms of internationalization and massification of enrolment have highlighted the growing concerns and crucial needs for quality and quality assurance in education. Proactive and responsive measures are continually in demand as important elements towards continuous improvement. Accreditations, peer reviews and quality audits are several external quality monitoring mechanisms that have been developed by quality assurance agencies with the motive to enhance accountability and improvement of quality. The first objective of this study is to take a proactive measure at an institutional level in developing an internal quality monitoring mechanism. With the motive for improvement, this mechanism is responsive to the stakeholders’ need for information in its development and in evaluating the quality of educational program by taking into consideration the issues and concerns of stakeholders as advance organizers of the evaluation. The foci of quality consist of quality as exceptional or excellence, quality as transformation and quality as fitness for purpose are designed and targeted at the output and outcome dimensions of a program which will complement the existing mechanisms that targeted only on inputs and processes. This developed internal quality monitoring mechanism is conceptually framed on the Logic Model for evaluation, modified Stake’s responsive evaluation approach, Bennett’s Targeting Outcomes of Programs Hierachy and utilizes Logic Model’s archetype indicators as its parameters…